Hazards of the Health Care Sector: Looking Beyond Infectious Disease - Melissa A. McDiarmid (Ubiquity Press, 2014)
Background: Possessing every hazard class, the health care sector poses significant health threats to its workforce in both high-resource settings and low- and middle-income countries (LMICs). Objectives: The aim of this paper was to examine the applicability of the classical hierarchy of hazard control technologies in resource-constrained health care settings. Methods: Using a biologic and chemical hazard example, the hazard control hierarchy was applied for risk mitigation. Findings: Even when resource constraints force a reordered selection of hazard control elements, risk reduction can be achieved across a variety of hazard classes. Conclusion: For LMICs with limited resources, the hazard control hierarchy can be effectively employed, although the selection of methods may be reordered, to achieve significant hazard control. Such prevention strategies can thereby strengthen and sustain a critical pillar of the health system, its workforce.